Characterization of a quantum bus between two driven qubits - Hijano, Alberto; Lyyra, Henri; Muhonen, Juha T.; Heikkilä, Tero T. (American Physical Society (APS), 2026)
We investigate the use of driven qubits coupled to a harmonic oscillator to implement a root iSWAP gate. By dressing the qubits through an external driving field, the qubits and the harmonic oscillator can be selectively coupled, allowing for the measurement of individual qubit states, as well as leading to effective qubit-qubit interactions. We compare the qubit readout on bare and dressed qubits, and demonstrate that when coupled to low-frequency resonators, dressed qubits provide a more robust readout than bare qubits in the presence of damping and thermal effects. Furthermore, we study the impact of various system parameters on the fidelity of the two-qubit gate, identifying an optimal range for quantum computation. Our findings guide the implementation of high-fidelity quantum gates in experimental setups, for example, those employing nanoscale mechanical resonators.